Prizes for basic research: Human capital, economic might and the shadow of history - Joshua Aizenman; Ilan Noy (University of California, Economics Department, 2006)
This paper studies the impact of global factors on patterns of basic research across countries and time. We rely on the records of major scientific awards, and on data dealing with global economic and historical trends. Specifically, we investigate the degree to which scale or threshold effects account for countries share of major prizes [Nobel, Fields, Kyoto and Wolf]. We construct a stylized model, predicting that lagged relative GDP of a country relative to the GDP of all countries engaging in basic research is an important explanatory variable of country's share of prizes. Scale effects imply that the association between the GDP share of a country and its prize share tends to be logistic - above a threshold, there is a take off range, where the prize share increases at an accelerating rate with the relative GDP share of the country, until it reaches maturity stage. Our empirical analysis confirms the importance of lagged relative GDP in accounting for countries' prize shares, and the presence of winner takes all scale effect benefiting the leader. Using measures of casualties during the wars, we find that the only significant effect can be found for a lag of 3 decades - i.e., deaths in the war negatively impact the viability of basic research about 30 years after the fact. With more recent data, we document the growing importance of countries that used to be at the periphery of global research, possibly advancing towards the take off stage.
Keywords: F15; F21; O3; N4; 330; Preisverleihung; Grundlagenforschung; Humankapital; Sozialprodukt; Welt